Early Vitamin A Supplementation for Prevention of Short-Term Morbidity and Mortality in Very-Low-Birth-Weight Infants: A Systematic Review and Meta-Analysis - Ye, Yanxiu; Yang, Xiaoyan; Zhao, Jing; He, Jianghua; Xu, Xiaoming; Li, Jiao; Shi, Jing; Mu, Dezhi (Frontiers in Pediatrics, 2022)
Background Vitamin A plays an important role in the development and maintenance of the normal function of organs and systems. Premature infants have low levels of vitamin A, which may be associated with an increased risk of developing disease. This study aimed to evaluate the effects of vitamin A supplementation on short-term morbidity and mortality in very-low-birth-weight (VLBW) infants. Methods We used PubMed, EMBASE, the Cochrane Central Register of Controlled Trials, and Web of Science to conduct a literature search of studies published before January 1, 2022, to be included in our meta-analysis. The analysis included randomized controlled trials that compared the effects of vitamin A supplementation on VLBW infants (birth weight <1,500 g) and controls given a placebo or no treatment. The certainty of evidence was assessed using Grading of Recommendations, Assessment, Development and Evaluation (GRADE) guidelines. Results Twelve randomized controlled trials were included in the meta-analysis, and 2,111 infants were pooled and analyzed. The overall risk of bias was not serious in the included studies. Vitamin A supplementation for reducing the incidence of bronchopulmonary dysplasia (BPD) at 36 weeks' postmenstrual age seems to be limited [risk ratio (RR):0.85; 95% confidence intervals (CI): 0.70–1.04; 8 studies, 1,595 infants, very-low-certainty evidence], which is different from the previous systematic review. Length of hospital stay (mean difference: −12.67, 95% CI: −23.55 to −1.79; 6 studies, 739 infants, low-certainty evidence), and the incidence of vitamin A deficiency at 28 days postnatal age (RR: 0.08; 95% CI: 0.02–0.38; 3 studies, 358 infants, low-certainty evidence) were reduced in the vitamin A group. Besides, vitamin A supplementation seems to reduce the incidence of periventricular leukomalacia (RR: 0.68; 95% CI: 0.47–0.97; 4 studies, 1,224 infants, low-certainty evidence) and retinopathy of prematurity of any grade (RR: 0.61; 95% CI: 0.48–0.76; 4 studies, 463 infants, moderate-certainty evidence). Conclusions There is no sufficient evidence regarding vitamin A supplementation preventing BPD in VLBW infants. Vitamin A supplementation can reduce the incidence of vitamin A deficiency and retinopathy of prematurity of any grade, and may exert an effect of preventing periventricular leukomalacia. Systematic Review Registration: http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42020211070.